Real estate for fusion: An anatomical comparison of surface area between cervical facet joints and the intervertebral disc space - Christopher Seidel; Clifford Pierre; Luke Jouppi; Luke DiPasquale; Chelsea Bush; Anna Anderson; Amit R. Patel (World Neurosurgery: X, 2025)
Introduction: Cervical stenosis may be treated surgically with anterior or posterior decompression with or without fixation. Recently, facet fusion using implantable devices using a posterior approach has been described as an alternative to anterior cervical discectomy and fusion (ACDF). To our knowledge, no anatomic studies have compared the surface area of the cervical facet joints to the intervertebral space. This study sought to provide a better understanding of the potential surface areas for arthrodesis. Methods: We performed a cross-sectional retrospective review using CT scans of the cervical spine in patients who had undergone imaging between 2014 and 2017. Using our institution's imaging software, we measured the area contained within the intervertebral space and the facet joints bilaterally. All surface area values for each intervertebral space were then compared using a paired t-test to the cumulative surface area of the facet joints calculated at each level. Results: Two hundred twelve patients (120 male, 92 female) were eligible for the analysis based on the inclusion and exclusion criteria. The mean age was 33 ± 6.0 years (range 18–55). The mean BMI was 29 ± 7.2 (range 19–58). In each of the comparisons, the combined intra-facet joint surface area (IFSA) was significantly greater than the intervertebral surface area (IVSA) of the corresponding interbody space. Conclusion: The surface area between the combined facet joints was almost two times greater than the intervertebral space. This may help establish an anatomic basis for comparable fusion results between the traditional ACDF and posterior fusion.